Stress of Elementary School teachers: environment in evidence (Research, Society and Development, 2020)
The selected objective was to describe the research environment of the elementary school teachers. We conducted a descriptive cross-sectional survey, with a quantitative approach. Results obtained from a sample of 421 surveyed teachers show that they are, 95.2% are women, in average, 41 years old, 43.9% hold a teaching licensure, with 15 years of teaching practice, 49% working just one educational institution and a daily average of 53 students. We verified that the teachers presented an intermediate stress level. The results also indicate that organizational and infrastructural factors are also correlated with stress levels. Overall, the results suggest that an inappropriate work environment is likely to generate an increased amount of stress in elementary school first grade teachers. Furthermore, this study brought an important debate on the work environment, highlighting the importance of being mindful to the teachers’ conditions in a work-related context. We suggest the development of new surveys on work environment and stress in elementary school teachers, with the implementation of environmental assessment tools, in order to comprehensively analyze the work environment.